Management considerations in grease versus non-grease scald burns in adults: A retrospective cohort study at a tertiary burn care facility - William Rice; Hemasree Yeluru; Miles Reese; Ricardo Rendel; Alexa Soult; Jessica Burgess (Burns Open)
Introduction: Scald burns are challenging to manage due to their evolutionary nature and nuanced injury pattern. Different mediums, such as hot water, steam, or grease, each have unique physical properties that may inflict more damage and incite a different inflammatory response. While pediatric patients are often the focus of scald burn research, a significant number of adults still suffer from scald burns, especially while cooking with hot grease. Our study aimed to analyze differences in injury pattern and management between grease versus non-grease scald burns. Materials and Methods: A retrospective chart review was done on all scald burn patients at a tertiary burn care center from January 2020 to December 2022. The primary outcomes were admission and length of stay with the primary exposure being grease versus non-grease scald burns. Secondary outcomes included rates of surgical excision and changes in surgical management plans. Multivariate regressions were employed to control for sex, age, total body surface area (TBSA), and burn thickness. Results: Of 165 patients with scald burns, 41 out of 91 (45.1 %) with grease burns and 43 out of 74 (58.1 %) with non-grease burns were admitted. No statistically significant difference in length of hospital stay existed between admitted grease and non-grease burns (p = 0.45). Additionally, no differences were observed for surgical excision (p = 0.63) and changes in surgical management plans (p = 0.47) Conclusion: The mechanism of scald burn caused by either a grease or non-grease source is not associated with any differences in admission, length of hospital stay, or surgical management. Scald burn management should still focus on patient age, TBSA, and burn thickness regardless of the causative agent.